Make in India: Perspective, Challenges and Opportunities - Dr. Kaushlendra Dixit (JOURNAL OF MANAGEMENT, SCIENCES, OPERATION & STRATEGIES, 2023)
Make in India campaign was launched in new Delhi by the Prime Minister Narendra Modi on 25th of September in 2014. It is an initiative to make a call to the top business investors all across the world (national or international) to invest in India. It is a big opportunity to all the investors to set up their business (manufacturing, textiles, automobiles, production, retail, chemicals, IT, ports, pharmaceuticals, hospitality, tourism, wellness, railways, leather, etc) in any field in the country. This attractive plan has resourceful proposals for the foreign companies to set up manufacturing powerhouses in India. Make in India campaign launched by the Indian government focuses on building the effective physical infrastructure as well as improving the market of digital network in the country to make it a global hub for business (ranging from satellites to submarines, cars to software’s, pharmaceuticals to ports, paper to power, etc). The symbol (derived from national emblem of India) of this initiative is a giant lion having many wheels (indicates peaceful progress and way to the vibrant future). A giant walking lion with many wheels indicates the courage, strength, tenacity and wisdom. The page of Make In India on the Facebook has crossed more than 120K likes and its twitter followers are more than 13K within few months of launching date. This national program is designed to transform the country into a global business hub as it contains attractive proposals for top local and foreign companies. This campaign focuses on creating number of valuable and honored jobs as well as skill enhancement in almost 25 sectors for improving the status of youths of the country. The sectors involved are automobiles, chemicals, IT & BPM, aviation, pharmaceuticals, construction, electrical machinery, food processing, defense manufacturing, space, textiles, garments, ports, leather, media and entertainment, wellness, mining, tourism and hospitality, railways, automobile components, renewable energy, mining, bio-technology, roads and highways, electronics systems and thermal power. The successful implementation of this plan will help in the 100 smart cities project and affordable housing in India. The main objective is to ensure solid growth and valuable employment creation in the country with the help of top investors. It will benefit both parties, the investors and our country. The government of India has created a dedicated help team and an online portal (makeinindia.com) for the easy and effective communication of investors. A dedicated cell is committed to answer all the queries from business entities anytime. Keywords: companies, manufacturing, electrical machinerym, employment creation.